227k views
4 votes
Factor this polynomial expression 10x^2-7x-12​

User Shaddow
by
5.2k points

2 Answers

6 votes

Answer:

(2x - 3)(5x + 4)

Explanation:

Given

10x² - 7x - 12

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 10 × - 12 = - 120 and sum = - 7

The factors are - 15 and + 8

Use these factors to split the x- term

10x² - 15x + 8x - 12 ( factor the first/second and third/fourth terms )

= 5x(2x - 3) + 4(2x - 3) ← factor out (2x - 3) from each term

= (2x - 3)(5x + 4) ← in factored form

User Nazar Kuliyev
by
5.6k points
4 votes


10x^2-7x-12=\\10x^2-15x+8x-12=\\5x(2x-3)+4(2x-3)=\\(5x+4)(2x-3)

User Juan Gonzales
by
5.2k points